Main Socio-economic factors explaining material deprivation among migrants in the EU28/EFTA before and after the 2015 immigration crisis. Differences with their native-born peers. - Ngouyamsa Mfondoum, Roland Bruno; Mazouch, Petr, 1981-; Brázdilová, Michaela; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2020)
This thesis analyses the position of migrants on material deprivation in the EU28/EFTA while testing for a possible change in their material deprivation conditions before and after the migration crisis of 2015, using the European Survey on Income and Living Conditions (EUSILC) of the years 2009 and 2018. It attempts to answer the questions of a possible difference in material deprivation risks and rates between non-EU migrants and locals’ households and of a structural change between the years analyzed. Material deprivation itself, defined as an enforced lack of a combination of items portraying some aspect of household living conditions, is reduced in this study to its economic strain dimension to allow a deeper review of each material deprivation intensity within the dimension. This research is therefore a uni-dimensional multilevel analysis of material deprivation of migrants at both macro and micro levels in the EU28/EFTA as a whole, while controlling for the countries differences and for the time effect between the years analyzed.
Vedoucí práce: Petr Mazouch
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: official statistics [obor dipl. práce]; diplomové práce; master's theses